Linear zones of increased oil producti vity in the carbonate reservoir of the Pushkarskoe area of Zimne-Stavkinsko-Pravoberezhnoye field - K. I. Chernenko; N. V. Yeriomina; Ye. Yu. Tumanova (Наука. Инновации. Технологии, 2022)
Introduction. The object of research is the carbonate deposit of the Neftekumsk suite of the Zimne-Stavkinsko-Pravoberezhnoye field (Pushkarskoye area), confined to the Lower Triassic deposits of the Eastern Stavropol. The purpose of the research is to increase the efficiency of oil field development based on the identification of zones of increased well productivity. To achieve this goal, the following tasks are supposed to be solved: assessment of the influence of tectonic and geodynamic factors; identification of zones of increased productivity of wells associated with a system of fractures accompanying zones of tectonic stresses discharge.Materials and methods of research. The materials included geological and field data on oil deposits (including well productivity), geophysical surveys of more than 200 deep wells, seismic data, satellite images of various scales, seismicgeological profiles, structural maps, isopach maps of effective oil saturated thicknesses, maps of current and cumulative recoveries and other materials of scientific and industrial enterprises. The following research methods were used: analysis, systematization and generalization of geological, geophysical and field data, the system-aerospace method, including the classical technology of interpretation of space images. The methodology developed by the authors for identifying zones of increased productivity of wells in carbonate deposits was used, taking into account satellite imagery interpretation data.Results and discussion. The analysis of zones of increased productivity of wells is given. It is established that these zones are predominantly linear in nature, and the linearity of the cumulative oil production does not depend on the time of putting the wells into operation. Structural factor, effective oil pay thickness, height above the contact, open porosity, oil saturation, specific oil reserves of the formation are not the determining factors of linearity. Based on the analysis of the geotectonic activity of the studied region, the influence of the geodynamic factor on well productivity was considered and it was revealed that zones of increased fracturing, which cause an increase in well productivity, are the result of tectonic stresses discharge. The established pattern of confinement of the directions of linear zones of increased fracturing is observed not only for carbonate Neftekumsk deposits, but also for terrigenous deposits in the upper part of the field crosssection.Conclusion. This methodology has been developed for identifying zones of increased fracturing and increased productivity of wells in the carbonate deposits of the Neftekumsk suite, due to the discharge of tectonic stresses, according to the directions of the lineaments of the day surface. The results of the research can be used to issue recommendations for identifying promising additional exploration objects for infill drilling and carrying out geological and technological measures to increase the recoverability of residual reserves.